2002
DOI: 10.1007/s00467-001-0813-y
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole: adjunctive therapy in steroid dependent minimal change nephrotic children

Abstract: In children with minimal change nephrotic syndrome (MCNS), the steroid dependent group constitutes an especially difficult case for management. Patients in this group are prone to serious steroid side effects. Additionally, alkylating agents commonly fail to maintain remission and expose patients to more side effects. Therapy with the immunostimulant drug levamisole may therefore be another option in the attempt to maintain remission with minimal side effects. We prospectively treated 20 of our steroid depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…duction in the relapse rate in SDNS patients. In a prospective trial, Donia et al [38] treated 20 SDNS patients with levamisole for 6 months and followed them for a further 6 months. At the end of the 6-month treatment period, 10 patients were maintaining remission on levamisole alone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…duction in the relapse rate in SDNS patients. In a prospective trial, Donia et al [38] treated 20 SDNS patients with levamisole for 6 months and followed them for a further 6 months. At the end of the 6-month treatment period, 10 patients were maintaining remission on levamisole alone.…”
Section: Discussionmentioning
confidence: 98%
“…The immunomodulatory agent levamisole has been used as an adjunctive therapy in such patients [31,32,33,34,35,36,37,38] as a good alternative to major immunosuppressives [39]. This treatment leads to decreases in the number of relapses and the amount of prednisolone required.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some patients remain steroid dependent despite this therapy. For these patients various therapeutic strategies have been suggested, including other immunosuppressive agents such as tacrolimus [3] or mycophenolate mofetil [4,5], or the immunostimulatory drug levamisole [6]. However, these strategies often fail to maintain complete remission of nephrotic syndrome [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is having an immunostimulating effect in immunosuppressed condition [5] but it has been found that it is also having a useful effect in autoimmune diseases like nephrotic syndrome and rheumatoid arthritis. It helps to make steroid free period of up to 6 months to 1 year in nephrotic syndrome [6,7]. Lactoferrin (Lac) is an 80 kDa multifunctional glycoprotein belonging to the transferrin family.…”
Section: Introductionmentioning
confidence: 99%